Debt Stabilization Bias and the Taylor Principle: Optimal Policy in a New Keynesian Model with Government Debt and Inflation Persistence. - Stehn, S; Vines, D (International Monetary Fund, 2007)
We analyse optimal monetary and fiscal policy in a New-Keynesian model with public debt and inflation persistence. Leith and Wren-Lewis (2007) have shown that optimal discretionary policy is subject to a 'debt stabilization bias' which requires debt to be returned to its pre-shock level. This finding has two important implications for optimal discretionary policy. Firstly, as Leith and Wren-Lewis have shown, optimal monetary policy in an economy with high steady-state debt cuts the interest rate in response to a cost-push shock--and therefore violates the Taylor principle. We show that this striking result is not true with high degrees of inflation persistence. Secondly, we show that optimal fiscal policy is more active under discretion than commitment at all degrees of inflation persistence and all levels of debt.